Delivering precision antimicrobial therapy through closed-loop control systems. (4th December 2017) - Rawson, T M; O'Hare, D; Herrero, P; Sharma, S; Moore, L S P; de Barra, E; Roberts, J A; Gordon, A C; Hope, W; Georgiou, P; Cass, A E G; Holmes, A H
Abstract: Sub-optimal exposure to antimicrobial therapy is associated with poor patient outcomes and the development of antimicrobial resistance. Mechanisms for optimizing the concentration of a drug within the individual patient are under development. However, several barriers remain in realizing true individualization of therapy. These include problems with plasma drug sampling, availability of appropriate assays, and current mechanisms for dose adjustment. Biosensor technology offers a means of providing real-time monitoring of antimicrobials in a minimally invasive fashion. We report the potential for using microneedle biosensor technology as part of closed-loop control systems for the optimization of antimicrobial therapy in individual patients.